2015
DOI: 10.1007/s10661-015-4689-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and chemical contamination of water, sediment and soil in the Nakivubo wetland area in Kampala, Uganda

Abstract: The reuse of domestic and industrial wastewater in urban settings of the developing world may harm the health of people through direct contact or via contaminated urban agricultural products and drinking water. We assessed chemical and microbial pollutants in 23 sentinel sites along the wastewater and faecal sludge management and reuse chain of Kampala, Uganda. Water samples were examined for bacteria (thermotolerant coliforms (TTCs), Escherichia coli and Salmonella spp.) and helminth eggs. Physico-chemical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 26 publications
(41 reference statements)
3
49
1
1
Order By: Relevance
“…antibiotics are those commonly used for treatment of various ailments in humans, thus strongly supporting the theories of introduction into the aquatic ecosystems from human associated sources. Studies along the Nakivubo channel in Uganda revealed presence of antibiotic residues in sediments, water and soil (Owino, 2014;Fuhrimann et al, 2015) with very low levels of gentamicin and ceftriaxolne which we also found were effective in this study.…”
Section: Resultssupporting
confidence: 73%
“…antibiotics are those commonly used for treatment of various ailments in humans, thus strongly supporting the theories of introduction into the aquatic ecosystems from human associated sources. Studies along the Nakivubo channel in Uganda revealed presence of antibiotic residues in sediments, water and soil (Owino, 2014;Fuhrimann et al, 2015) with very low levels of gentamicin and ceftriaxolne which we also found were effective in this study.…”
Section: Resultssupporting
confidence: 73%
“…It has also to be considered that the potential uptake of animals A. caninum eggs does not necessarily mean that relevant amounts of animals faeces need to be taken up, since eggs may have been attached to food. In fact, many studies report the presence of hookworm eggs in food 43,44 and also in water 45 . However, this a very low probability since twelve A. caninum eggs were found in the respective patient.…”
Section: Discussionmentioning
confidence: 99%
“…Such a system ideally includes both microbial and chemical indicators and is coupled to a pre-defined response for the event that parameter values are above set limits. Such an early warning system would not only allow to recognise trends and seasonal variability of specific health hazards but also enhance a more proactive protection of urban farming communities and consumers of their produce (WHO, 2006;Fuhrimann et al, 2015).…”
Section: Proposed Control Measures Along the Wastewater Systemsmentioning
confidence: 99%